Fault tolerant cloud auditing - Muhammed Yusof, Zulkefli; Shah, Asadullah; Waqas, Ahmad (2013)
The aim of cloud computing is to deliver on-demand services to its users with guarantee of scalability, availability and reliability. These services have a variety that may include simple and complex software, infrastructure and architecture. It may vary according to the Cloud Service Provider (CSP) and the service license agreement (SLA) with Cloud Client. The research contribution in this paper has two facets. First, an investigative review on cloud computing services, models, security and privacy concerns, and auditing strategies is conducted. Secondly, we suggest the fault tolerant approach in conjunction with the tiered strategy for cloud auditing.